2020
DOI: 10.3390/ijms21249636
|View full text |Cite
|
Sign up to set email alerts
|

Cell Fusion of Mesenchymal Stem/Stromal Cells and Breast Cancer Cells Leads to the Formation of Hybrid Cells Exhibiting Diverse and Individual (Stem Cell) Characteristics

Abstract: Cancer is one of the most common diseases worldwide, and treatment bears many challenges such as drug and radioresistance and formation of metastases. These difficulties are due to tumor heterogeneity, which has many origins. One may be cell fusion, a process that is relevant in both physiological (e.g., wound healing) and pathophysiological (cancer and viral infection) processes. In this study, we examined if cell fusion between mesenchymal stem/stromal cells (MSCs) and breast cancer (BC) cells occurs and if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…Moreover, hybrids exhibited increased expression levels of the stem cell transcription factors Oct4, Sox2, Nanog, Kif4 as well as Bmi1, suggesting that they may have acquired stem cell-like properties [27]. Similar data were presented by Dörnen et al demonstrating that the fusion of MSCs and breast cancer cells led to the formation of tumor hybrids exhibiting diverse and individual (stem cell) characteristics [40]. In vitro and in vivo studies of Melzer and colleagues showed that human MSCs could fuse with human breast cancer cells and that tumor hybrids possessed an enhanced metastatic capacity to distant organs in a much shorter period of time than the parental breast cancer cells [60,61,65].…”
Section: In Vitro and In Vivo Data Supporting Cell-cell Fusion In Cancersupporting
confidence: 72%
See 1 more Smart Citation
“…Moreover, hybrids exhibited increased expression levels of the stem cell transcription factors Oct4, Sox2, Nanog, Kif4 as well as Bmi1, suggesting that they may have acquired stem cell-like properties [27]. Similar data were presented by Dörnen et al demonstrating that the fusion of MSCs and breast cancer cells led to the formation of tumor hybrids exhibiting diverse and individual (stem cell) characteristics [40]. In vitro and in vivo studies of Melzer and colleagues showed that human MSCs could fuse with human breast cancer cells and that tumor hybrids possessed an enhanced metastatic capacity to distant organs in a much shorter period of time than the parental breast cancer cells [60,61,65].…”
Section: In Vitro and In Vivo Data Supporting Cell-cell Fusion In Cancersupporting
confidence: 72%
“…Most studies focusing on heterotypic cell-cell fusion events have investigated tumor hybrids that were derived from cancer cells and macrophages or stem cells. This might be attributed to the fact that both macrophages and stem cells possess fusogenic capacities [20][21][22][23][24][25][26][27][30][31][32][33][34][35][36][38][39][40]52]. For instance, it is well known that macrophages give rise to multinucleated osteoclasts through hybridization [7,53,54] and that stem cells could restore degenerated tissues by cell-cell fusion [55][56][57][58].…”
Section: In Vitro and In Vivo Data Supporting Cell-cell Fusion In Cancermentioning
confidence: 99%
“…Beyond providing insight on tumor protein expression, our detection of mutant KRAS genes in CHCs isolated from a patient with PDAC highlights their promise as source of genomic material to facilitate tumor profiling for clinically actionable oncogenic alterations. Given that KRAS mutations were only identified in a subset of CHCs underscores there is much that remains to be understood about hybrid cell biology, including the degree to which hybrid cells retain each parent genome and the process of ploidy reduction 55 . Additionally, evidence exists of allele recombination between parent genomes resulting in genetically distinct hybrid cells and contributes to the heterogeneity of hybrid cell populations 56 .…”
Section: Discussionmentioning
confidence: 99%
“…This assumption would be in agreement with data revealing that fusion of non-transformed cells could give rise to transformed and tumorigenic hybrids exhibiting CS/IC properties [ 70 , 97 , 142 ]. Moreover, cancer cells could also acquire CS/IC properties by fusion with stem cells as demonstrated in several studies [ 22 , 26 , 29 , 44 , 143 , 144 , 162 , 163 ]. In more detail, gene expression analysis of hybrids after fusion of lung-cancer cells with MSC revealed markedly increased expression levels of the cancer stem-cell markers CD44 and CD133 and the overall stemness markers Oct4, Nanog, Sox2, Kif4 and Bmi1, which supports the assumption that cancer cells may acquire CS/IC properties through fusion with stem cells [ 26 ].…”
Section: Therapeutic and Clinical Consequences Of Cancer-cell Fusionmentioning
confidence: 99%
“…However, these processes may not be mutually exclusive. As discussed above, some studies suggested that cancer cells could acquire CS/ICs properties via cell fusion [ 22 , 26 , 29 , 44 , 143 , 144 , 162 , 163 ]. If so, cell-fusion-derived CS/ICs would not only be more tumorigenic and metastatogenic, but should also acquire an increased resistance against radiation and cytotoxic compounds according to the defined characteristics of cancer stem cells [ 160 , 161 , 178 , 179 , 180 ].…”
Section: Therapeutic and Clinical Consequences Of Cancer-cell Fusionmentioning
confidence: 99%